Prostorska in razvojna vprašanja Alp - Nared, Janez (Georitem, 2009)
The Alps are one of the most sensitive regions in Europe, and their future development represents a challenge that demands the cooperation of various experts, the business world, politics, and society, as well as the people living there. The Interreg IIIB project DIAMONT, which took place from 2005 to 2008, also addressed Alpine developmental challenges. This monograph presents the basic results of the project, supported by the broader theoretical framework of regional and sustainable development. We first present the cultural differences in the Alps and their influence on sustainable regional development. This is followed by the results of a Delphi analysis, which helped reveal the basic development tendencies in the Alps, and then we discuss appropriate indicators for regional development and harmonizing data. Attention is then dedicated to regional development instruments and the participative process, which is essential for attaining truly sustainable development. Finally, we present a Slovenian perspective on these issues.